Better Security Through Obfuscation: The quest to find greater security through obscurity. - Edwards, Chris (Communications of the ACM, 2021)
The article discusses efforts by computer scientists and mathematicians to improve computer security and privacy by hiding the interior mechanisms of computer software via indistinguishability obfuscation (iO). It describes the functions of iO, breakthroughs in iO research, and a potential method of iO implementation and delivery.